2018
DOI: 10.3390/w10040416
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Model for Annual Runoff Time Series Forecasting Using Elman Neural Network with Ensemble Empirical Mode Decomposition

Abstract: Because of the complex nonstationary and nonlinear characteristics of annual runoff time series, it is difficult to achieve good prediction accuracy. In this paper, ensemble empirical mode decomposition (EEMD) coupled with Elman neural network (ENN)-namely the EEMD-ENN model-is proposed to reduce the difficulty of modeling and to improve prediction accuracy. The annual runoff time series from four hydrological stations in the lower reaches of the four main rivers in the Dongting Lake basin, and one at the outl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…However, these models require that the time series be stationary and have a large number of data points for a robust forecasting result. Nonlinear data-driven models, such as the Artificial Neural Network (ANN), with its advantage of learning and identifying complex data patterns with less data, has captured significant attention in precipitation, rainfall, runoff, drought, evapotranspiration and temperature forecasting problems in the past few years [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. However, one of the major challenges faced by ANN is that it requires an iterative adjustment of model parameters, a slow response of the gradient-based learning algorithm used, and a relatively low prediction accuracy compared with more advanced NN algorithms [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these models require that the time series be stationary and have a large number of data points for a robust forecasting result. Nonlinear data-driven models, such as the Artificial Neural Network (ANN), with its advantage of learning and identifying complex data patterns with less data, has captured significant attention in precipitation, rainfall, runoff, drought, evapotranspiration and temperature forecasting problems in the past few years [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. However, one of the major challenges faced by ANN is that it requires an iterative adjustment of model parameters, a slow response of the gradient-based learning algorithm used, and a relatively low prediction accuracy compared with more advanced NN algorithms [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 30 ] proposed a hybrid model that utilized the EEMD coupled with ANN for long-term runoff forecasting. Zhang et al [ 31 ] adopted the EEMD coupled with the Elman Neural Network (ENN) for annual runoff time series forecasting. Their research results demonstrated that the EEMD coupled with other popular methods can significantly improve time series forecasting precision compared with some other popular methods.…”
Section: Introductionmentioning
confidence: 99%
“…They additionally proposed an ANN-based model designed to overcome this limitation and listed the improved features of the developed model for irregular rainfall-runoff prediction based on the results obtained by applying the model to catchments in the Mediterranean region. Zhang et al [14] used an Elman neural network to improve the prediction accuracy of the time-series runoff input data by taking into account the nonlinear characteristics of the data. They proposed a water level prediction model for warning purposes by considering the hidden layer for lead time (t − 1) along with the originally predicted time (t).…”
Section: Introductionmentioning
confidence: 99%
“…Niu et al [33] applied the EEMD combined with LSSVM for day-ahead PM2.5 concentration prediction and obtained accurate results. Zhang et al [34] proposed a new hybrid model, EEMD with Elman neural network, for annual runoff time series forecasting in the Dongting Lack basin, and the results showed that this proposed model gave a good performance. The hybrid forecasting model formed by combining VMD with other algorithms has been successfully applied in many fields.…”
Section: Introductionmentioning
confidence: 99%